Terahertz Spin-Conductance Spectroscopy: Probing Coherent and Incoherent Ultrafast Spin Tunneling - Rouzegar, Reza; Wahada, Mohamed Amine; Chekhov, Alexander L; Hoppe, Wolfgang; Bierhance, Genaro; Jechumtál, Jiří; Nádvorník, Lukáš; Wolf, Martin; Seifert, Tom S; Parkin, Stuart S P; Woltersdorf, Georg; Brouwer, Piet W; et al. (Nano letters, 2024)
Thin-film stacks F|H consisting of a ferromagnetic-metal layer F and a heavy-metal layer H are spintronic model systems. Here, we present a method to measure the ultrabroadband spin conductance across a layer X between F and H at terahertz frequencies, which are the natural frequencies of spin-transport dynamics. We apply our approach to MgO tunneling barriers with thickness d = 0-6 Å. In the time domain, the spin conductance Gs has two components. An instantaneous feature arises from processes like coherent spin tunneling. Remarkably, a longer-lived component is a hallmark of incoherent resonant spin tunneling mediated by MgO defect states, because its relaxation time grows monotonically with d to as much as 270 fs at d = 6.0 Å. Our results are in full agreement with an analytical model. They indicate that terahertz spin-conductance spectroscopy will yield new and relevant insights into ultrafast spin transport in a wide range of spintronic nanostructures.
Keywords: incoherent resonant tunneling; MgO tunnel junctions; spin conductance; Terahertz spintronics; terahertz spectroscopy; coherent tunneling